2019
DOI: 10.1101/712828
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Super-resolution microscopy unveils FIP200-scaffolded, cup-shaped organization of mammalian autophagic initiation machinery

Abstract: 12Autophagy is an essential physiological process by which eukaryotic cells degrade and recycle 13 cellular materials. Although the biochemical hierarchies of the mammalian autophagy pathway 14 have been identified, questions remain regarding the sequence, subcellular location, and 15 structural requirements of autophagosome formation. Here, we characterize the structural 16 organization of key components of the mammalian autophagic initiation machinery at ~20 nm 17 spatial resolution via three-color, three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…On the other hand, the FIP200 dimer gives rise to a C shape, in contrast to the S shape of Atg17 ( Ragusa et al, 2012 ). The Atg17 S has been postulated to have a unique role in nucleating cup-shaped phagophores in bulk autophagy ( Bahrami et al, 2017 ) on the basis of first-principles physical membrane modeling, something that would not be achieved by a C. Cup-shaped FIP200 structures have been visualized in amino acid–starved U2OS cells by super-resolution microscopy ( Kenny et al, 2019 Preprint ), likely corresponding to phagophores observed in cells by EM ( Hayashi-Nishino et al, 2009 ; Ylä-Anttila et al, 2009 ). The ∼20-nm diameter of the FIP200 C shape is potentially compatible with localization on highly curved ATG9 vesicles or on the rim of the growing phagophore.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the FIP200 dimer gives rise to a C shape, in contrast to the S shape of Atg17 ( Ragusa et al, 2012 ). The Atg17 S has been postulated to have a unique role in nucleating cup-shaped phagophores in bulk autophagy ( Bahrami et al, 2017 ) on the basis of first-principles physical membrane modeling, something that would not be achieved by a C. Cup-shaped FIP200 structures have been visualized in amino acid–starved U2OS cells by super-resolution microscopy ( Kenny et al, 2019 Preprint ), likely corresponding to phagophores observed in cells by EM ( Hayashi-Nishino et al, 2009 ; Ylä-Anttila et al, 2009 ). The ∼20-nm diameter of the FIP200 C shape is potentially compatible with localization on highly curved ATG9 vesicles or on the rim of the growing phagophore.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, although the components of the autophagy machinery can be recruited to p62 condensates, at least to some extent, independently of FIP200, the spatial organization of ATG13 and ULK1 as well as ATG9A was disturbed upon FIP200 deletion. The arrangement of FIP200 around p62 condensates is reminiscent of the localization of FIP200 and ATG13 in starvation induced autophagy (Karanasios et al, 2016;Kenny et al, 2019) and the frequently observed FIP200 protrusions might represent the sites where the autophagy machinery establishes contacts with the ER (Karanasios et al, 2016, Kenny et al, 2019. FIP200 might thus spatially organize ATG9A vesicles and the ULK1 complex allowing these components to come in contact with the PI3KC3-C1 for subsequent PI3P production.…”
Section: Super-resolution Microscopy Of P62 Condensates Reveals a Posmentioning
confidence: 90%
“…and it appeared as a cup-shaped structure by super-resolution microscopy (Kenny, Chen et al, 2019). Recently, electron microscopy analysis of purified ULK1-ATG13-FIP200 complex, revealed that the N-terminal domain of FIP200 forms a C-shaped scaffold which organizes the other subunits of the complex (Shi, Yokom et al, 2020).…”
mentioning
confidence: 99%
“…On the other hand, the FIP200 dimer gives rise to a C shape, in contrast to the S-shape of Atg17 (Ragusa et al, 2012). The Atg17 S has been postulated to have a unique role in nucleating cup-shaped phagophores in bulk autophagy (Bahrami et al, 2017) on the basis of first-principles physical membrane modeling, something that would not be achieved by a C. Cup-shaped FIP200 structures have been visualized in amino acid-starved U2OS cells by super-resolution microscopy (Kenny, 2019), likely corresponding to phagophores observed in cell by EM (Hayashi-Nishino et al, 2009;Yla-Anttila et al, 2009). The ~20 nm diameter of the FIP200 C shape is potentially compatible with localization on highly curved ATG9 vesicles or on the rim of the growing phagophore.…”
Section: Discussionmentioning
confidence: 99%